William Golding - Medcalf, Stephen (Writers and Their Work Series., 1975)
William Golding has observed, that an appropriate epigraph, for his writings would be a remake attributed to St Augustine, 'Woe be to me if I speak of God: woe be to me if I do not speak of God', and has written again that 'Modern man is appallingly ignorant of his own nature.' The energy generated in this conflict between a sense of the utter impossibility of writing honestly about the profound and the intimate in the human condition, and a sense of vocation.